2003
DOI: 10.1103/physrevc.67.064604
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic predictions of exclusive208Pb(p,2p)

Abstract: Within the framework of the relativistic distorted wave impulse approximation (DWIA), we investigate the sensitivity of the analyzing power -for exclusive proton knockout from the 3s 1/2 , 2d 3/2 and 2d 5/2 states in 208 Pb, at an incident laboratory kinetic energy of 202 MeV, and for coincident coplanar scattering angles (28.0 • , −54.6 • ) -to different distorting optical potentials, finite-range (FR) versus zero-range (ZR) approximations to the DWIA, as well as medium-modified coupling constants and meson m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The formalism for the relativistic distorted wave model has been presented in Refs. [2,4,5,6,7]. In this paper we briefly allude to the most important aspects of the model and refer the interested reader to the latter references for more detail.…”
Section: Relativistic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The formalism for the relativistic distorted wave model has been presented in Refs. [2,4,5,6,7]. In this paper we briefly allude to the most important aspects of the model and refer the interested reader to the latter references for more detail.…”
Section: Relativistic Modelmentioning
confidence: 99%
“…The corresponding nonrelativistic prediction, indicated by the dashed line in Fig. (1), completely fails to describe the data despite exhaustive corrections including different kinematic prescriptions for the NN amplitudes, non-local corrections to the scattering wave functions, and density-dependent modifications to the free NN scattering amplitudes [1,2]. On the other hand, both Dirac and Schrödinger-equation-based models provide an excellent description of the unpolarized energy-sharing cross section, thus highlighting the application of spin observables, such as the analyzing power, for discriminating between different dynamical effects in nuclear systems.…”
Section: Introductionmentioning
confidence: 99%
“…(III)] and, in particular, study the sensitivity of exclusive ( p, 2 p ) polarization transfer observables to these representations. In a previous paper we demonstrated the importance of including distorting optical potentials on the incident and outgoing scattering wave functions for a correct description of ( p, 2p) analyzing powers [2]. However, in order to simplify the present analysis, we consider a relativistic plane wave model, whereby all distorting optical potentials are set equal to zero in the Dirac equation.…”
Section: Relativistic Plane Wave Impulse Approximationmentioning
confidence: 99%
“…Recently, we demonstrated that a model based on the relativistic distorted wave impulse approximation (DWIA) provides an almost perfect description of exclusive ( p, 2p) analyzing power data, whereas corresponding nonrelativistic Schrödinger-equation-based predictions completely fail [1,2,3]. For both dynamical models, however, the comparison of theoretical predictions to unpolarized cross section data yields similar spectroscopic factors which are also in good agreement with those extracted from (e, e ′ p) studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation